Parallel curriculum model: An evaluation on students’ academic achievement and motivation in profession of education course - Wiwit Artika; Dewi Andayani; Maulida Maulida; Hendra Yulisman (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2025)
A suitable teaching model and strategy are essential to enhance student motivation and learning in the classroom, following the semester program evaluation meeting results in the biology education department for the 2023/2024 academic year. The Parallel Curriculum Model (PCM) is a curriculum framework designed to provide appropriately challenging and differentiated learning experiences that increase intellectual engagement. This experimental design study explores PCM’s impact on student learning outcomes, identifies the PCM parallel group with the highest achievement, and assesses its effect on student motivation. The participants included 78 students enrolled in the Profession of Education course. Academic avhievement was evaluated through case analysis-based pre- and post-test essays, analyzed using t-tests, while motivation was measured with the ARCS motivation model, then categorized by levels. Findings reveal that PCM positively influenced student performance, and motivation levels were high. This suggests that using PCM as a teaching strategy can be an effective alternative to enhance students’ academic success. Moreover, incorporating ARCS motivation principles into curriculum design can contribute to more dynamic learning environments and improved academic results.Abstrak. Model dan strategi pengajaran yang tepat sangat penting untuk meningkatkan motivasi dan pembelajaran siswa di kelas, sebagai tindak lanjut dari hasil evaluasi program semester di departemen pendidikan biologi tahun akademik 2023/2024. Parallel Curriculum Model (PCM) adalah kerangka kurikulum yang dirancang untuk memberikan pengalaman belajar yang menantang dan terdiferensiasi secara tepat, yang dapat meningkatkan keterlibatan intelektual siswa. Penelitian dengan desain eksperimen ini bertujuan untuk mengeksplorasi dampak PCM terhadap hasil belajar siswa, mengidentifikasi kelompok paralel PCM dengan pencapaian tertinggi, serta menilai pengaruhnya terhadap motivasi siswa. Partisipan dalam penelitian ini adalah 78 mahasiswa yang terdaftar dalam mata kuliah Profesi Pendidikan. Pencapaian akademik dievaluasi melalui esai pre-test dan post-test berbasis analisis kasus, yang kemudian dianalisis dengan uji t, sementara motivasi diukur dengan model motivasi ARCS dan dikategorikan berdasarkan tingkatannya. Hasil penelitian menunjukkan bahwa PCM memiliki pengaruh positif terhadap kinerja akademik siswa, dan tingkat motivasi siswa berada pada kategori tinggi. Hasil ini menunjukkan bahwa penggunaan PCM sebagai strategi pengajaran dapat menjadi alternatif efektif untuk meningkatkan prestasi akademik siswa. Selain itu, penerapan prinsip-prinsip motivasi ARCS dalam desain kurikulum dapat menciptakan lingkungan belajar yang lebih dinamis dan meningkatkan hasil akademik.